2021
DOI: 10.1128/spectrum.00067-21
|View full text |Cite
|
Sign up to set email alerts
|

Early Neonatal Meconium Does Not Have a Demonstrable Microbiota Determined through Use of Robust Negative Controls with cpn 60-Based Microbiome Profiling

Abstract: Much like the recent placental microbiome controversy, studies of neonatal meconium reporting bacterial communities within the fetal and neonatal gut imply that microbial colonization begins prior to birth. However, recent work has shown that placental microbiomes almost exclusively represent contamination from lab reagents and the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…We profiled the microbiomes of 623 maternal vaginal swabs taken on admission to labour and delivery, 142 meconium samples, 581 stool samples from 10-day-old infants and 462 stool samples from 3-month-old infants. Data for LEGACY meconium samples have been described elsewhere, demonstrating lack of a detectable microbiome signature that could be differentiated from background signal and no evidence of an in-utero stool microbiome ( Dos Santos et al., 2021 ). Following quality control, 71,826,602 reads were retained from 621 vaginal microbiomes, 570 10-day stool microbiomes, 460 3-month stool microbiomes and 176 controls.…”
Section: Resultsmentioning
confidence: 99%
“…We profiled the microbiomes of 623 maternal vaginal swabs taken on admission to labour and delivery, 142 meconium samples, 581 stool samples from 10-day-old infants and 462 stool samples from 3-month-old infants. Data for LEGACY meconium samples have been described elsewhere, demonstrating lack of a detectable microbiome signature that could be differentiated from background signal and no evidence of an in-utero stool microbiome ( Dos Santos et al., 2021 ). Following quality control, 71,826,602 reads were retained from 621 vaginal microbiomes, 570 10-day stool microbiomes, 460 3-month stool microbiomes and 176 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Enterobacter and Escherichia, commonly identified contaminants in laboratory and extraction kit reagents [65,66] have been reported as the most abundant genera detected in amniotic fluid [67,68] . Similarly, controlled studies have reported that the microbial content of meconium does not differ from negative controls [69,70] . A recent study claimed to have detected bacterial DNA and viable bacteria in the fetal intestine using 16S rRNA gene sequencing, qPCR, electron microscopy, and bacterial culture of Micrococcus luteus-related bacteria, which appeared to show adaptations to the fetal environment, re-igniting the controversy surrounding the existence of in utero microbiomes [71,72] .…”
Section: In Utero Microbiome Transfermentioning
confidence: 88%
“… 91 93 This “ in utero colonization theory” leaves open the possibility of a maternal–fetal efflux of commensal bacteria, 87 providing another framework of how prenatal air pollution exposure could more directly influence an infant’s intestinal microbiome. However, the presence of bacteria in meconium samples is also debated, because studies 94 , 95 reported that the bacteria found in the majority of the “dogma-challenging” studies originated from contamination from lab reagents and the environment. During childhood, black carbon particles may also be transported into the gut after mucociliary clearance of particles from the airways or systemic uptake after inhalation.…”
Section: Discussionmentioning
confidence: 99%